Electrochemical Anodizing Treatment to Enhance Localized Corrosion Resistance of Pure Titanium. Issue 1 (26th January 2017) - Prando, Davide; Brenna, Andrea; Bolzoni, Fabio M.; Diamanti, Maria V.; Pedeferri, Mariapia; Ormellese, Marco
Background: Titanium has outstanding corrosion resistance due to the thin protective oxide layer that is formed on its surface. Nevertheless, in harsh and severe environments, pure titanium may suffer localized corrosion. In those conditions, costly titanium alloys containing palladium, nickel and molybdenum are used. This purpose investigated how it is possible to control corrosion, at lower cost, by electrochemical surface treatment on pure titanium, increasing the thickness of the natural oxide layer. Methods: Anodic oxidation was performed on titanium by immersion in H2 SO4 solution and applying voltages ranging from 10 to 80 V. Different anodic current densities were considered. Potentiodynamic tests in chloride- and fluoride-containing solutions were carried out on anodized titanium to determine the pitting potential. Results: All tested anodizing treatments increased corrosion resistance of pure titanium, but never reached the performance of titanium alloys. The best corrosion behavior was obtained on titanium anodized at voltages lower than 40 V at 20 mA/cm 2 . Conclusions: Titanium samples anodized at low cell voltage were seen to give high corrosion resistance in chloride- and fluoride-containing solutions. Electrolyte bath and anodic current density have little effect on the corrosion behavior.